Incorporating local content stories into innovative e-book development for high school students in Central Kalimantan, Indonesia - Misrita, Misrita; Ikrimah, Ikrimah; Bahing, Bahing (Journal on English as a Foreign Language, 2024)
Many studies have shown the enhancement of student engagement by integrating local content into digital learning resources. However, little is known about the interactively and culturally relevant materials in incorporating customizable and engaging content for students. The present study aims to develop an e-book focusing on narrative texts that incorporate local content stories for high school students in Central Kalimantan, Indonesia. This research and development study utilized the ADDIE model and TPACK framework. The research involved 35 students in the eleventh grade at the senior high school. It also involved three English teachers and three external validators. Data were garnered through questionnaires, observations and interviews. The quantitative data were analyzed using descriptive statistics analysis, and qualitative data were analyzed using thematic analysis. Results show that expert validation indicated high-quality media presentation and local content integration. In addition, students